2007
DOI: 10.1177/0146167206296299
|View full text |Cite
|
Sign up to set email alerts
|

Liberty and Justice for All? Implications of Exposure to the U.S. Flag for Intergroup Relations

Abstract: Three studies examined the implications of nationalistic ideologies and exposure to the U.S. flag for the activation of egalitarian concepts and outgroup hostility. Study 1 demonstrated that subliminal exposure to the U.S. flag activated participants' egalitarian concepts. In Study 2, highly nationalistic participants who were exposed to the U.S. flag reported less hostility than did those not exposed to the flag, whereas the flag did not influence the hostility of participants low in nationalism. Study 3 demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 21 publications
10
87
3
Order By: Relevance
“…They speak in particular to the implicit influence of one of the most visible symbols in the American cultural and political landscape-the American national flag. Evidently, the kinds of information that are repeatedly and saliently presented in reference to the nation can be implicitly activated for some people as soon as they perceive symbols of the nation (see also Butz et al, 2007;Devos & Banaji, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They speak in particular to the implicit influence of one of the most visible symbols in the American cultural and political landscape-the American national flag. Evidently, the kinds of information that are repeatedly and saliently presented in reference to the nation can be implicitly activated for some people as soon as they perceive symbols of the nation (see also Butz et al, 2007;Devos & Banaji, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, are American symbols associated with the values and principles that are commonly identified as part of the American ethos, such as liberty and justice? Interestingly, Butz et al (2007) recently found that American symbols do seem to be associated with egalitarianism, at least for those participants who highly identify with the nation. The fact that America seems to be associated with an implicit pro-White bias on one hand (Devos & Banaji, 2005) and egalitarianism on the other speaks to the purported richness of information and knowledge associated with such familiar, highly visible cultural icons (see Betsky, 1997;Ortner, 1973Ortner, , p. 1339.…”
Section: Implicit Effects Of American Symbolsmentioning
confidence: 99%
“…For example, Butz, Plant, and Doerr (2007) showed that the U.S. flag is associated with egalitarianism and that exposure to the flag reduces hostile nationalistic attitudes toward Muslims and Arabs by increasing the influence of egalitarianism on these judgments. Addressing a similar process, Ehrlinger et al (2011) discovered that exposure to the Confederate flag decreases positive attitudes toward Barack Obama.…”
Section: A Theory Of Motivated Political Reasoning and The Activationmentioning
confidence: 99%
“…Butz, Plant, and Doerr (2007) found that highly nationalistic Americans were less hostile toward outgroup (Arabs and Muslim) after being exposed to the American national flag. How can this result be reconciled with the classic principle that ingroup identity salience leads to rejection of outgroup members (Tajfel & Turner, 1979)?…”
Section: Discussionmentioning
confidence: 96%